2007
DOI: 10.1007/s10526-007-9103-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of phytohormones in basal resistance and Trichoderma-induced systemic resistance to Botrytis cinerea in Arabidopsis thaliana

Abstract: Thirty-six phytohormone-affected mutants of Arabidopsis thaliana (L.) Heynh. and their parental ecotypes were tested for resistance/susceptibility to Botrytis cinerea Pers.; Fr. and ability to develop Trichoderma-mediated induced systemic resistance (ISR). Ecotype Colombia-0 (Col-0) was relatively resistant to B. cinerea, and Trichoderma harzianum Rifai T39 application at sites spatially separated (roots) from the B. cinerea inoculation (leaves) resulted in reduction of grey mold symptoms. Ecotypes Wassilewski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
3
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 33 publications
9
75
3
4
Order By: Relevance
“…In accordance with previous studies in which root application of T. harzianum or T. atroviride was able to reduce the leaf lesion area caused by B. cinerea (49,54,55), T. parareesei T6 also triggered ISR against this foliar pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies in which root application of T. harzianum or T. atroviride was able to reduce the leaf lesion area caused by B. cinerea (49,54,55), T. parareesei T6 also triggered ISR against this foliar pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…The ISR triggered by Trichoderma occurs through the JA/ET signalling pathway similarly to PGPR-ISR (Shoresh et al, 2005), as confirmed by several authors: (i) cerato-platanin Sm1 is required for T. virens-mediated ISR against Colletotrichum graminicola in maize (Djonovic et al, 2007), (ii) Trichoderma treatment of JA/ET-deficient Arabidopsis genotypes leads to enhanced susceptibility to Botrytis cinerea (Korolev et al, 2008), (iii) ISR triggered by PGPR and Trichoderma converges upstream from MYB72, an early key component of the onset of ISR (Segarra et al, 2009). However, other studies have shown that in the T. asperellum-cucumber interaction the induction of plant responses is a time-and concentration-dependent phenomenon, and in the first hours of contact a SARlike response is observed, with an increase in SA and peroxidase activity.…”
Section: Defence Signalling Pathways Induced By Trichodermamentioning
confidence: 57%
“…Likewise, ISR triggered by the PGPF Penicillium sp. GP16-2, Trichoderma harzianum T39 and P. indica was shown to be blocked in JAand ET-signaling mutants of Arabidopsis (Hossain et al, 2008;Korolev et al, 2008;Stein et al, 2008).…”
Section: Ja-and Et-dependent Signalingmentioning
confidence: 97%